Challenges and Opportunities of SEND Inclusion Classrooms for English Language Teachers in Doha, Qatar/Dissertation Submitted to the University of Derby in Partial Fulfilment of the Requirements for the Degree of Master of Arts in Education - Jaber Riham (2019)
Abstract, Introduction, Rationale, Aims and Purpose of the Study, Review of the Literature, Introduction, SEND Students' Right to Education, English Language as a Necessity, SEND English Language Inclusion, Teacher Perspective on SEND Inclusion, Challenges of SEND Inclusion Classrooms, Resources and Support of SEND Inclusion, General Policies and SEND Inclusion in Qatar, MADA, Cross-Sectoral Services, Transition Challenges, Teaching Strategies Used to Implement SEND, Methodology, Introduction, Research Methodology and Epistemology of the Research, Data Collection and Interviews, Data Collection and Tools, Sampling, Data Analysis, Ethical Considerations, Reliability and Validity of the Study, Findings and Analysis and Discussion, Teacher Perspective on Imclusion, Opportunities, Challenges, Discussion, What are Teachers' Perspectives on the Approach of Inclusive Classrooms in Doha, Conclusions and Recommendations, Reerences, Appendices.